2020
DOI: 10.1111/acem.14092
|View full text |Cite
|
Sign up to set email alerts
|

Disparities in Care: The Role of Race on the Utilization of Physical Restraints in the Emergency Setting

Abstract: Objective: Race-based bias in health care occurs at organizational, structural, and clinical levels and impacts emergency medical care. Limited literature exists on the role of race on patient restraint in the emergency setting. This study sought to examine the role of race in physical restraint in an emergency department (ED) at a major academic medical center. Methods: Retrospective chart analysis was performed, querying all adult ED visits over a 2-year period (2016-2018) at Massachusetts General Hospital. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
66
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(70 citation statements)
references
References 14 publications
4
66
0
Order By: Relevance
“…Studies in adult populations have demonstrated significant associations between Black race and an increased risk of being physically restrained in an emergency department setting (Wong et al, 2020). This association between race and restraint usage has also been shown in adult emergency settings, even when controlling for sex, insurance, age, diagnosis, homelessness, and history of violence (Schnitzer et al, 2020). Data is limited in pediatric settings, though some recent studies have found associations between restraint/seclusion usage and race as well as gender and psychiatric diagnosis in inpatient and residential settings (Vidal et al, 2020; Braun et al, 2020; Donovan et al, 2003).…”
Section: Previous Studiesmentioning
confidence: 68%
“…Studies in adult populations have demonstrated significant associations between Black race and an increased risk of being physically restrained in an emergency department setting (Wong et al, 2020). This association between race and restraint usage has also been shown in adult emergency settings, even when controlling for sex, insurance, age, diagnosis, homelessness, and history of violence (Schnitzer et al, 2020). Data is limited in pediatric settings, though some recent studies have found associations between restraint/seclusion usage and race as well as gender and psychiatric diagnosis in inpatient and residential settings (Vidal et al, 2020; Braun et al, 2020; Donovan et al, 2003).…”
Section: Previous Studiesmentioning
confidence: 68%
“…Among patients hospitalized for Covid-19 at MGH, 35% were Hispanic, although Hispanic patients comprised 8% of inpatient discharges at MGH in 2017, 1% of emergency department visitors in 2018, and 20% of the population of Boston [9][10][11]. This reflects the disproportionate burden of Covid-19 among communities in the MGH catchment area as well as at other Boston area academic medical centers, who also observed a high proportion of hospitalized Table 1.…”
Section: Discussionmentioning
confidence: 99%
“…We read with interest the manuscript by Schnitzer et al 1 on the role of race in physical restraint use and the accompanying invited commentary by Corbin et al 2 We commend the effort put forth in this study as management of agitated patients is a challenging but often overlooked problem. In addition, we agree that racial bias likely exists with regard to physical restraint use, as described in the mental health literature 3 and by Dr. Corbin's personal experiences as an African American emergency physician.…”
mentioning
confidence: 95%